PEMBELAJARAN BAHASA ARAB MELALUI KEMAMPUAN MUHADATSAH - Kaharuddin Kaharuddin (Al-Ishlah: Jurnal Pendidikan Islam, 2018)
One of the skills learned in learning Arabic language is maharah al-kalam(speaking skill). Muhadatsah (conversation) which is one part of maharah alkalamis a skill that is used to communicate for thoughts, thoughts for others. theability of Muhadatsah in learning Arabic, helps something that is easy, by thosewho must pay attention to various factors and always look for patterns and systemsthat can really overcome learning problems. To be able to learn effectiveMuhadatsah learning, it must look for various things, starting from attend,selection of methods, techniques and selection of appropriate materials withstudents.